A bioinspired ionic diode membrane based on sub-2 nm covalent organic framework channels for ultrahigh osmotic energy generation. (January 2023) - Gao, Mengyao; Zheng, Min-Jie; EL-Mahdy, Ahmed F.M.; Chang, Chen-Wei; Su, Yu-Chun; Hung, Wen-Hsin; Kuo, Shiao-Wei; Yeh, Li-Hsien
Abstract: Electric eels can convert ionic concentration gradients into a high-efficiency power via a large number of sub-2 nm transmembrane ion channels, which can exhibit high ion selectivity and strong diode-like ion rectification property. Inspired by this, herein, we report on a sub-2 nm scale ionic diode membrane, composed of an ultrathin (∼110 nm) β-ketoenamine-linked two-dimensional covalent-organic framework (COF) membrane and a highly ordered alumina nanochannel membrane (ANM), for highly efficient osmotic energy harvesting. As verified by our experimental and simulation results, the heterostructured membrane with the features of asymmetric charges and pore sizes in two aligned COF (1.1 nm) and ANM (100 nm) channels is capable of highly rectifying ion transport even in high 0.5 M salt solution. Benefiting from the presence of abundant sub-2 nm COF-based ion channels and the strong ionic diode effect, an unprecedented power density of up to 27.8 W/m 2 is achieved by mixing the artificial salt-lake water and river water (500-fold NaCl gradient). This study will open new avenues of using the rectified ion channel-mimetic nanofluidic membrane as a new platform towards the exploration and development of an ultrahigh osmotic power generator. Graphical Abstract: ga1 Highlights: The sub-2 nm-scale COF-based ionic diode membrane has been developed for efficient osmotic energy conversion. The ion channel-mimetic nanofluidic membrane can rectify ion transport even in seawater simulated solution. A record power density of 27.8 W/m 2 is achieved by mixing artificial salt-lake and river water. Simulations attribute the breakthrough power output to the numerous sub-2 nm 1D COF channels and strong ionic diode effect.